Factors Influencing the Performance of Health Workers at Pattingalloan Community Health Center, Pinrang Regency - Satria, Muhammad Aji; Hilintang, Rendhar Putri; Syahrir, Muhammad Sabri (Indonesian Scientific Publication, 2025)
This study aims to analyze how leadership, motivation, and discipline influence the performance of healthcare workers at Puskesmas Pattingalloan, Kabupaten Pinrang, Indonesia. Workforce performance is a key determinant of service quality, especially in rural and resource-limited contexts. Using a quantitative cross sectional design, data were collected from 98 health workers through validated Likert scale questionnaires and analyzed using chi square tests and ordinal logistic regression. The results show that leadership, motivation, and discipline significantly affect performance. Participative and communicative leadership styles were strongly linked to higher productivity and staff commitment. Health workers with high levels of intrinsic and extrinsic motivation were notably more consistent and effective in service delivery. Likewise, strong adherence to disciplinary standards, including punctuality and professional responsibility, correlated with improved performance and patient satisfaction. These findings reinforce existing theories on transformational leadership and motivational dynamics, especially within decentralized healthcare systems. This study offers valuable policy implications for strengthening human resource management at the primary care level. Integrating leadership development, sustainable motivation programs, and supportive disciplinary frameworks can foster a culture of accountability and efficiency. The insights generated contribute to the global discourse on healthcare workforce optimization and provide direction for future empirical studies.